Maqāṣid al-Sharī‘ah and the Prohibition of Incest in Indonesian Legislation: An Analysis of the Protection of Lineage and Public Morals - Sukataman; Idlofi; Agung Nugroho Reformis Santono; Umar Chamdan (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2025)
The phenomenon of incestuous marriage in Indonesia continues to occur despite being strictly prohibited by Islamic law and national positive law. This paper discusses the issue of incest from the perspective of maqāṣid al-sharī‘ah, highlighting how the principles of ḥifẓ al-nasab (protection of lineage) and ḥifẓ al-‘irḍ (protection of morality and honour) serve as the normative and ethical basis for the prohibition of incestuous marriage. This study uses a qualitative approach based on normative and comparative legal analysis of classical Islamic legal sources, national legislation such as the Marriage Law, KHI, and KUHP, and developing social phenomena. The results of the study show that the maqāṣid al-sharī‘ah approach uses ṣalah al-uṣūl al-khamsah, ḥifẓ al-nasl, to formulate the prohibition of incest. Ḥifẓ al-nasl consists of two elements: wujūd (productive) and 'adam (protective). The prohibition of incest is a form of protective behaviour, similar to the prohibitions of adultery and qażf. The application of maqāṣid al-sharī‘ah to positive law can offer new possibilities for Indonesian law, which is expected to encompass legal, social, and moral aspects.